RECENT DISCOVERIES IN MEXICO AND GUATEMALA - CASO (My University, 1939)
EXCAVATIONS on Monte Alban in the State of Oaxaca, MEX, the site on which the rich grave treasure of gold and other ornaments was found in January of last year, were resumed at the end of October by Senor Alfonso Caso on an extended scale immediately t
NATURE
Keywords: RECENT DISCOVERIES, MEXICO, GUATEMALA; MULTIDISCIPLINARIA; CIENCIAS AUXILIARES DE LA HISTORIA; ARQUEOLOGIA